2012
DOI: 10.1016/j.jep.2012.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of Cordyceps on lung fibrosis in cellular and rat models

Abstract: The findings provide an insight into the preventive and therapeutic potentials of Cordyceps for the treatment of lung fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…13,14 In addition, cordycepin can activate AMPKα and inhibit oxidative stress. [15][16][17] However, no research has been performed to elucidate the effect of cordycepin on cardiac hypertrophy. The purpose of this study was to determine whether cordycepin can attenuate cardiac hypertrophy, induced by 1 μmol/L Ang II in cultured neonatal rat cardiac myocytes in vitro and by pressure overload in mice.…”
mentioning
confidence: 99%
“…13,14 In addition, cordycepin can activate AMPKα and inhibit oxidative stress. [15][16][17] However, no research has been performed to elucidate the effect of cordycepin on cardiac hypertrophy. The purpose of this study was to determine whether cordycepin can attenuate cardiac hypertrophy, induced by 1 μmol/L Ang II in cultured neonatal rat cardiac myocytes in vitro and by pressure overload in mice.…”
mentioning
confidence: 99%
“…O. sinensis also has obvious therapeutic and health care effects on other organ systems and diseases, such as antimicrobial activities (Mamta et al ., ), protection of lung (Chen et al ., ) and liver (Wang et al ., ) functions, therapeutic effects on diabetes (El Ashry et al ., ; Liu et al ., ) and asthma (Kuo et al ., ). Studies also found that O .…”
Section: Functional Activities and Mechanisms Of O Sinensismentioning
confidence: 99%
“…Other therapeutic and health care potentialities O. sinensis also has obvious therapeutic and health care effects on other organ systems and diseases, such as antimicrobial activities (Mamta et al, 2015), protection of lung (Chen et al, 2012) and liver (Wang et al, 2012a) functions, therapeutic effects on diabetes (El Ashry et al, 2012;Liu et al, 2016) and asthma (Kuo et al, 2001). Studies also found that O. sinensis can increase hypoxia tolerance (Singh et al, 2013) and ATP levels on muscle strength, power output and endurance (Chen et al, 2014a;Kumar et al, 2011).…”
Section: Prevention Of Osteoporosismentioning
confidence: 99%
“…However, most studies on Cordyceps are animal studies, in vitro studies, or ex vivo studies, and conclusions on the efficacy of Cordyceps are difficult to make 22 24 . A systematic review on the efficacy of Cordyceps in treating chronic kidney disease found no definite conclusion due to the poor quality of evidence 20 .…”
Section: Cordycepsmentioning
confidence: 99%